2015
DOI: 10.1177/1074248415583090
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Attenuates Aortic Endothelial Permeability and Arteriosclerosis in Streptozotocin-Induced Diabetic Rats

Abstract: The development of diabetic macrovascular complications is a multifactorial process, and melatonin may possess cardiovascular protective properties. This study was designed to evaluate whether melatonin attenuates arteriosclerosis and endothelial permeability by suppressing the myosin light-chain kinase (MLCK)/myosin light-chain phosphorylation (p-MLC) system via the mitogen-activated protein kinase (MAPK) signaling pathway or by suppressing the myosin phosphatase-targeting subunit phosphorylation (p-MYPT)/p-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 47 publications
(56 reference statements)
1
17
0
Order By: Relevance
“…Serum NO levels were measured using a commercial kit (Jiancheng, Nanjing, China). The insulin sensitivity index was calculated using the [1/(FBG × fasting insulin)] formula ( 18 ). All analyses were performed in duplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Serum NO levels were measured using a commercial kit (Jiancheng, Nanjing, China). The insulin sensitivity index was calculated using the [1/(FBG × fasting insulin)] formula ( 18 ). All analyses were performed in duplicate.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to MAPK signaling, a recent study showed that melatonin decreased aortic endothelial permeability and atherosclerosis in a mouse model of diabetes by decreasing the expression of myosin light chain kinase (MLCK), myosin phosphatase-targeting subunit phosphorylation, and myosin light-chain phosphorylation. Melatonin also decreased upstream expression of extracellular signal-related kinase (ERK) and p38 [ 51 ]. Zhu et al [ 52 ] found that micro ribonucleic acid-29b (miR-29b) promotes endothelial permeability and apoptosis in high-fat diet-fed apoE knock-out mice by down-regulating the expression of MT1, which is a melatonin receptor.…”
Section: Melatonin and Vascular Diseasesmentioning
confidence: 99%
“…[45] Later on, it was suggested that melatonin modulated the mitogen-activated protein kinase (MAPK) signal transduction pathway. Tang et al, in a study on diabetic mouse, demonstrated that melatonin reduced the aortic endothelial permeability and atherosclerosis following treatment with melatonin, [46] which could have resulted from the reduction of the expression of myosin light chain kinase (MLCK), myosin phosphatase [targeting subunit phosphorylation], and myosin light-chain phosphorylation acting via extracellular signal-related kinase (ERK/p38) signal transduction pathway.. [46] In another recent study which was conducted on high-fat diet fed rats and induced diabetic rats, melatonin was reported to reverse the endothelial function and vascular responses. [47] A double-blind, randomized, controlled trial study on 39 patients (32 men and 7 women) with three vessels coronary disease has revealed that melatonin have beneficial effects on endothelial oxidative stress even in patient with severe and advanced atherosclerosis.…”
Section: Cardiovascular Systemmentioning
confidence: 99%